Lack of recovery of the long-spined sea urchin Diadema antillarum Philippi in Puerto Rico 30 years after the Caribbean-wide mass mortality - Tuohy,Evan; Wade,Christina; Weil,Ernesto (PeerJ, 2020)
Caribbean populations of the long-spined black sea urchin Diadema antillarum Philippi were decimated by a disease-induced mass mortality in the early 1980’s. The present study provides an updated status of the D. antillarum recovery and population characteristics in La Parguera Natural Reserve, Puerto Rico. The last detailed study to assess population recovery in 2001, indicated a slow, and modest recovery, albeit densities remained far below pre-mass mortality levels. Population densities were assessed along three depth intervals in six reef localities and one depth in three lagoonal sea-grass mounds using ten 20 m2 (10 × 2 m) belt-transects at each depth interval. Most of these were previously surveyed in 2001. All individuals encountered along the belt transects were sized in situ with calipers and rulers to characterize the size (age) structure of each population and get insight into the urchin’s population dynamics and differences across localities in the area. Habitat complexity (rugosity) was assessed in all depth intervals. No significant differences in population densities between reef zones (inner shelf and mid-shelf) were observed, but significantly higher densities were found on shallow habitats (<5 m depth; 2.56 ± 1.6 ind/m2) compared to intermediate (7–12 m; 0.47 ± 0.8 ind/m2) and deep (>12 m; 0.04 ± 0.08 ind/m2) reef habitats in almost all sites surveyed. Habitat complexity had the greatest effect on population densities at all levels (site, zone and depth) with more rugose environments containing significantly higher densities and wider size structures. Comparison between survey years revealed that D. antillarum populations have not increased since 2001, and urchins seem to prefer shallower, more complex and productive areas of the reef. Populations were dominated by medium to large (5–9 cm in test diameter) individuals and size-frequency distributions indicated that smaller juveniles were virtually absent compared to 2001, which could reflect a recruitment-limited population and explain in part, the lack of increase in population densities. The limited temporal scale of this study, high horizontal movement of individuals along the complex, shallower reef and inshore habitats could also explain the general decline in mean densities. Other extrinsic factors affecting reproductive output and/or succesful recruitment and survival of juveniles likely contribute to the high variablility in population densities observed over time.
Keywords: Diadema antillarum; Mass mortality; Population status; Puerto Rico